2016
DOI: 10.1158/1078-0432.ccr-15-0499
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E1 Inhibition can Overcome Sorafenib Resistance in Hepatocellular Carcinoma Cells Through Mcl-1 Suppression

Abstract: Purpose: To clarify the effects of cyclin E1 suppression on antitumor efficacy of sorafenib in hepatocellular carcinoma cells and to explore the potential of combining sorafenib with cyclindependent kinase (CDK) inhibition in therapy.Experimental Design: The effects of cyclin E1 suppression on sorafenib-induced apoptosis were tested in both sorafenibsensitive (Huh-7 and HepG2, IC 50 5-6 mmol/L) and sorafenib-resistant (Huh-7R and HepG2R, IC 50 14-15 mmol/L) hepatocellular carcinoma cells. The activity of perti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…3B). Hsu et al (10) suggested that Mcl-1 suppression is critical to restore sorafenib-induced apoptosis in sorafenib-resistant HCC cells. The present results revealed that amentoflavone not only decreased sorafenib-induced anti-apoptotic protein levels (XIAP, Mcl-1 and C-FLIP) but also triggered sorafenib-induced pro-apoptotic protein expression (cleaved-Caspase-3, -8 and cytochrome c) in SK-Hep1R cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). Hsu et al (10) suggested that Mcl-1 suppression is critical to restore sorafenib-induced apoptosis in sorafenib-resistant HCC cells. The present results revealed that amentoflavone not only decreased sorafenib-induced anti-apoptotic protein levels (XIAP, Mcl-1 and C-FLIP) but also triggered sorafenib-induced pro-apoptotic protein expression (cleaved-Caspase-3, -8 and cytochrome c) in SK-Hep1R cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle and anti-apoptosis associated proteins are overexpressed by sorafenib treatment in sorafenib-resistant HCC cells. In addition, Hsu et al (10) proposed that Cyclin-E1 and myeloid cell leukemia-1 (Mcl-1) overexpression inhibits sorafenib-induced apoptosis, whereas suppression of Cyclin-E1 and Mcl-1 enhances induction of apoptosis. Based on these previous studies, it was hypothesized that restoration of sorafenib-induced apoptosis by sorafenib sensitizers is a critical mechanism in overcoming sorafenib resistance in HCC cells.…”
Section: Amentoflavone Enhances Sorafenib-induced Apoptosis Through Ementioning
confidence: 99%
“…69 Furthermore, the growth-inhibitory and apoptosis-inducing effects of sorafenib were enhanced by flavopiridol in HCC cells, and cyclin E1 inhibition can overcome sorafenib resistance. 70 Cyclin D was downregulated by lenvatinib in primary anaplastic thyroid cancer cells, which might further affect CDK4 and CDK6. 71 Palbociclib is the first clinically available CDK4/6 inhibitor for treating metastatic breast cancer approved by the FDA.…”
Section: Cyclin-dependent Kinase 4/6mentioning
confidence: 95%
“…Additionally, CDK4 and cyclin D1 could be inhibited by sorafenib, simultaneously increase expression of Fas, Fas‐L, and caspase‐3, and decreased the ratio of Bcl‐2 to Bax . Furthermore, the growth‐inhibitory and apoptosis‐inducing effects of sorafenib were enhanced by flavopiridol in HCC cells, and cyclin E1 inhibition can overcome sorafenib resistance . Cyclin D was downregulated by lenvatinib in primary anaplastic thyroid cancer cells, which might further affect CDK4 and CDK6 …”
Section: Biology and Regulation Of Cdks In Hccmentioning
confidence: 99%
“…The changes of representative genes related to T-cell activation and function were confirmed by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) (The primer list for qRT-PCR and detailed methods are described in online suppl. Table S1) [31].…”
Section: Development Of Orthotopic Liver Cancer Modelsmentioning
confidence: 99%